2015
DOI: 10.1016/j.diff.2015.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Sry-type HMG box 18 contributes to the differentiation of bone marrow-derived mesenchymal stem cells to endothelial cells

Abstract: Objective Mesenchymal stem cells (MSC) have shown therapeutic potential to engraft and either differentiate into or support differentiation of vascular endothelial cells (EC), smooth muscle cells and cardiomyocytes in animal models of ischemic heart disease. Following intracoronary or transendocardial delivery of MSCs, however, only a small fraction of cells engraft and the majority of those persist as an immature cell phenotype. The goal of the current study was to decipher the molecular pathways and mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…Our group recently demonstrated that Sox18 mediates VEGF-A-induced differentiation of bone marrow-derived MSCs into ECs [21]. In tandem with VEGF-A, IL-6 caused a dose-dependent increase in IL-6R mRNA and a dose-dependent decrease in VEGFR-2 mRNA (Figure 3(a)) and Sox18 protein (Figure 3(b)).…”
Section: Resultsmentioning
confidence: 96%
“…Our group recently demonstrated that Sox18 mediates VEGF-A-induced differentiation of bone marrow-derived MSCs into ECs [21]. In tandem with VEGF-A, IL-6 caused a dose-dependent increase in IL-6R mRNA and a dose-dependent decrease in VEGFR-2 mRNA (Figure 3(a)) and Sox18 protein (Figure 3(b)).…”
Section: Resultsmentioning
confidence: 96%
“…We also found that the expression level of Sox18 was up regulated during the differentiation process through VEGFR-II. Additionally, we found that MSCs deficient in Sox18 maintain their undifferentiated phenotype (Ikhapoh et al, 2015). These results provided evidence that the overexpression of Sox18 in MSCs stimulates the translation of EC markers (Ikhapoh et al, 2015).…”
Section: Myogenic Differentiationmentioning
confidence: 91%
“…Additionally, we found that MSCs deficient in Sox18 maintain their undifferentiated phenotype (Ikhapoh et al, 2015). These results provided evidence that the overexpression of Sox18 in MSCs stimulates the translation of EC markers (Ikhapoh et al, 2015). Therefore, Sox18 is a critical regulator of MSC differentiation to ECs which can provide a new clinical application of MSC therapy in cardiovascular disease.…”
Section: Myogenic Differentiationmentioning
confidence: 91%
See 1 more Smart Citation
“…These factors can induce profound changes in the capacity for MSC, drive its differentiation into CAFs 111,114,115 , and produce growth factors 29,35,39 and angiogenic 112,115 and metastatic cytokines 118-121 . These findings suggest that MSCs may participate in the pathogenic vicious cycle wherein tumor cells modify stromal cells, and in turn, MSCs promote malignant cell maintenance and tumor growth via plastic and biochemical changes in the tumor microenvironment ( Figure1 ).…”
Section: Mscs and Tumor Microenvironmentmentioning
confidence: 99%